Reduced PKC α Activity Induces Senescent Phenotype in Erythrocytes. (4th September 2012) - Govekar, Rukmini B.; Kawle, Poonam D.; Advani, Suresh H.; Zingde, Surekha M.
Abstract : The molecular mechanism mediating expression of senescent cell antigen-aggregated or cleaved band 3 and externalized phosphatidylserine (PS) on the surface of aged erythrocytes and their premature expression in certain anemias is not completely elucidated. The erythrocytes with these surface modifications undergo macrophage-mediated phagocytosis. In this study, the role of protein kinase C (PKC) isoforms in the expression of these surface modifications was investigated. Inhibition of PKCα by 30  μ M rottlerin (R30) and 2.3 nM Gö 6976 caused expression of both the senescent cell marker-externalized PS measured by FACS analysis and aggregated band 3 detected by western blotting. In contrast to this observation, but in keeping with literature, PKC activation by phorbol-12-myristate-13-acetate (PMA) also led to the expression of senescence markers. We explain this antithesis by demonstrating that PMA-treated cells show reduction in the activity of PKCα, thereby simulating inhibition. The reduction in PKCα activity may be attributed to the known downregulation of PMA-activated PKCα, caused by its membrane translocation and proteolysis. We demonstrate membrane translocation of PKCα in PMA-treated cells to substantiate this inference. Thus loss of PKCα activity either by inhibition or downregulation can cause surface modifications which can trigger erythrophagocytosis.